Towards Blockchain for Suitable Efficiency and Data Integrity of IoT Ecosystem Transactions - Nivetha, M.; Gokulraj, S. (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
This article analyzes the effectiveness of the usage of blockchain technology to enforce IoT environment database. To this give up, we have a look at the performance of transactions that occur on clever device and the integrity more often than not by way of analytical modeling based on queuing standards. In this situation, the common transaction confirmation time is taken into consideration. the usage of his flips, statistical integrity is measured thru simulations that provide the scammer the opportunity to alternate the information that are already saved. In addition, the test remembers some contingencies associated with wonderful utility domain names. The cease outcomes display that blockchain era cannot only offer fantastic truth integrity however also meet the performance requirements of the IoT. Finally, favorable conclusions and extra research possibilities conclude this text.